2014
DOI: 10.3354/meps10888
|View full text |Cite
|
Sign up to set email alerts
|

Degradation state of algal diets affects fatty acid composition but not size of red urchin gonads

Abstract: Kelps in temperate marine ecosystems produce substantial detrital biomass that provides a carbon subsidy to consumers. After detachment, detrital kelp degrades and potentially changes in nutritional quality. Red sea urchins Mesocentrotus franciscanus are an abundant consumer of drift algae, but little is known about the effects of kelp degradation on feeding preferences or nutritional value to urchins. We compared the response of gonad index (GI), carbon and nitrogen stable isotope (SI) content, and fatty acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
(90 reference statements)
1
10
0
1
Order By: Relevance
“…For example, experiments have identified EPA as a strong predictor of growth in cladoceran zooplankton [ 23 , 24 ], and isopods [ 25 ]. Increased dietary arachidonic ARA correlates with improved growth in juvenile bivalves [ 26 ], gonad development in sea urchins [ 27 29 ], and higher fecundity in marine copepods [ 30 ]. DHA is critical to fish larval development [ 31 33 ], and copepod egg viability [ 34 ], and egg-production rates [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, experiments have identified EPA as a strong predictor of growth in cladoceran zooplankton [ 23 , 24 ], and isopods [ 25 ]. Increased dietary arachidonic ARA correlates with improved growth in juvenile bivalves [ 26 ], gonad development in sea urchins [ 27 29 ], and higher fecundity in marine copepods [ 30 ]. DHA is critical to fish larval development [ 31 33 ], and copepod egg viability [ 34 ], and egg-production rates [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Past feeding experiments with S. droebachiensis have shown, for example, that they have considerable ability to modify their dietary FA over long experiments (14 week duration; Kelly et al, 2008), or that they do not incorporate their dietary FA signal into their tissues in very short experiments (3 week duration; Wessels et al, 2012). A long (17 week) feeding experiment with adult red urchins (Mesocentrotus franciscanus) showed that urchin FAs were strongly differentiated in the gonad tissues of urchins fed two kelp species (Raymond et al, 2014). Our results show that when fed for a sufficiently long period (e.g., 25 weeks in S. droebachiensis, 10 weeks in S. purpuratus), both urchins' multivariate FA compositions are strongly affected by their diets; in fact, both species can be differentiated based on whether they were fed brown, red, and green algae (NMDS and PERMANOVA results).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these differences, particularly between urchin species and life stage, it is nonetheless clear that growing urchins, whether from increased tissue biomass, or in gonad development, incorporated multivariate FA profiles of the algae provided. The macroalgal diets selected here are known to have strong differences in their FA; future work could investigate whether it is possible to trace the FA of more closely related algae, e.g., different species of Laminariales (e.g., Raymond et al, 2014), into these urchin species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…I collected fresh N. luetkeana from kelp beds in the San Juan Channel on the day of the experiment. To simulate detached drift bull kelp, I aged non-reproductive blades in a black-plastic covered outdoor tank with flowing seawater for one week prior to the feeding experiment ( Raymond, Lowe & Galloway, 2014 ). As in the other electivity experiments, each crab was offered an approximately 10 × 30 cm piece of fresh (mean mass ± SE = 17.6 ± 1.4 g) and aged bull kelp (mean mass ± SE = 21.3 g ± 1.6 g) in a choice experiment.…”
Section: Methodsmentioning
confidence: 99%